Implementasi Pojok Baca Kelas dalam Mendorong Partisipasi Siswa pada Kegiatan Literasi - Fitri Widiajaya; Susiati S.; Anin Asnidar; Idrus Ramli (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to describe the implementation and analyze the impact of the Classroom Reading Corner (PBK) on the participation of Grade IX students in literacy activities at UPT SMPN 1 Galesong Selatan. The background issue was the formal atmosphere and access barriers in the school library, which led to low reading initiative among students. The solution implemented was the transformation of a class corner into an attractive, easily accessible, and text-rich Reading Corner. The implementation method involved needs analysis, design, implementation, and evaluation using a Likert Scale questionnaire. The questionnaire respondents were 40 students from class IX.C. The result of the questionnaire analysis showed an average agreement score of 4.2 out of 5, categorized as High. This result indicates that PBK successfully created a comfortable environment, increased accessibility, and effectively encouraged student participation and initiative to read outside of formal class hours. The program contributes significantly to strengthening the literacy culture at the classroom level.